Um estudo sobre a validade do modelo exponencial do BJT visando a lineariza??o de amplificadores de pot?ncia em FM - Silveira, Daniel Discini (2003)
The task of optimizing or making feasible the implementation of amplifiers with better efficiency and linearity would be facilitated if a complete analytical model of the BJT transistor were developed, since from this it would be possible to construct more efficient linearizers, not only in terms of cost, but also Operation. The initial objective of this work was to investigate the potentiality of the simple nonlinear analytical models proposed by Clarke-Hess to quantify the behavior of BJT in large signal RF amplifiers. Once the coherence of the Clarke-Hess model was verified, the main objective of the work was to investigate whether it could be implemented for two-tone analysis, which would allow analytical determination of the intermodulation products generated by the PN junction and others Results of great interest. Analytical tests were performed for one tone and the results were compared to numerical simulation results with ADS (MBH). Next, an actual amplifier was tested using a high frequency BJT transistor. After confirming the potential of the model, the analysis was extended to two input tones, searching for the determination of parameters essential to the characterization of a non-linear device, and the values ??obtained were compared to the ADS. The reasonable convergence between analytical methods and ADS software has demonstrated that the Clarke-Hess model and the new deduced equations have the potential to approximate values ??of the numerical model used by the ADS, providing a reliable analytical source for linearizers.